Parallel cellular programming skeleton - Saez, Fernando (2009)
Cellular automata provide an abstract model of parallel com- putation that can be effectively used for modeling and simulation of com- plex phenomena and systems. The design and implementation of parallel programming languages based on skeletons simplify the design, test and code of parallel algorithms. We discuss here the main characteristics of cellular automata programming models and we show a cellular automata skeleton for the exploitation on the inherent parallelism of problems of this kind. As a practical example, we show how to solve the problem of heat equation through the skeleton.